A novel activated carbon material from peanut shells for the removal of methyl orange and methylene blue dyes from wastewater: kinetics, isotherms and mechanism - Oluwagbemi Aladeokin; Ashleigh Fletcher (Adsorption Science & Technology)
This study investigated the removal of methyl orange (MO) and methylene blue (MB) dyes from an aqueous phase using a novel activated carbon material derived from peanut shells. The effects of pH, contact-time and initial dye concentration on the adsorption performance were evaluated. The adsorption kinetics were fitted with pseudo-first-order, pseudo-second-order and intraparticle diffusion models, while the adsorption isotherms were modelled using Langmuir, Freundlich and Sips equations. The results showed that the adsorption of both dyes followed the PSO kinetic model, and the Freundlich and Sips isotherm models. The maximum adsorption capacities of the carbon material for MO and MB, according to the Sips model, were 4584 and 1769 mg/g, respectively. The pH range of 3–11 had negligible influence on the adsorption capacities of both dyes. The adsorption mechanism was mainly attributed to π–π interactions, n–π electron donor–acceptor (EDA) interactions and pore filling. The activated carbon material exhibited good reusability and stability, achieving over 90% dye removal, after five cycles of adsorption–desorption using hot (90 ± 2 °C) deionised water as the eluent, indicating that the carbon material synthesised from peanut shells is a promising adsorbent for the removal of ionic dyes from wastewater.